Mechanical Behavior of Concrete Materials and Structures Experimental Evidence and Analytical Models - De Domenico, Dario; Almeida Bernardo, Luís Filipe (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint contains 15 papers published in the Special Issue entitled "Mechanical Behavior of Concrete Materials and Structures: Experimental Evidence and Analytical Models". Dealing with the broad spectrum of the mechanical behavior of concrete materials and structures, the reprint includes experimental findings and numerical analyses using both conventional and advanced methodologies. This book presents contributions in the field of not only ordinary and prestressed concretes, but also special concretes, including high-strength, recycled, and fiber-reinforced concretes, for both structural and non-structural applications, and for the development of related numerical/analytical predictive models.